Armed conflict and human rights law : protecting civilians and international humanitarian law - Odon, Daniel Ivo (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book explores developments in international law regarding the relationship between human rights law and international humanitarian law and their co-applicability in armed conflict situations. The work examines the jurisprudence of the international human rights courts, and looks at the Inter American and European Human Rights Courts' caselaw in dealing with new emergencies in armed conflicts. It argues that a new interpretation and application of the law is required to deal with current needs while remaining faithful to moral commitments made in the international arena. In this way, the book deals with recent cases and their rationale to build a new understanding of law and international policy that complies with the globalization process and progress towards an enhancement of the international community's legal framework. Combining the emergencies in armed conflicts with the mutual enforcement of human rights law and humanitarian law, this book holistically develops concepts and theories to present a pragmatic solution to moral quandaries over the targeting of civilians during armed conflict situations. The book will be a valuable resource for academics, researchers and policy-makers in the areas of International Human Rights and International Humanitarian Law"--
Introduction -- Contemporary international law and the sense of community -- The law of human rights -- The law of armed conflicts -- The interplay between international humanitarian law and human rights law -- Conclusion.
Keywords: International law and human rights; Humanitarian law; Civilians in war; War -- Protection of civilians; Combatants and noncombatants (International law); LAW / General; LAW / Civil Rights; LAW / Comparative